Fault-tolerant output-feedback stabilization for complex-valued neural networks with time delay and actuator failures - Cancan Zhou; Muyun Fang; Jianwei Xia; Jianping Zhou; Zhen Wang (AIP Advances, 2019)
The paper considers the issue of fault-tolerant output-feedback stabilization for complex-valued neural networks with both time delay and actuator failures. The aim is to design a fault-tolerant output-feedback controller to ensure the network to be asymptotically stable. By using the discretized Lyapunov-Krasovskii functional method as well as the free-weighting matrix approach, a delay-dependent stability criterion is proposed. Then, with the aid of some decoupling techniques, a method for the design of desired output-feedback fault-tolerant controller is developed. Finally, a numerical example is given to verify the effectiveness of the present stabilizing method.